Editorial (Medical Forum Monthly, 2024)
A World Bank report has warned that malnutrition costs countries up to 3.0 percent of the yearly GDP and malnourished children lose 10 percent of their lifetime earning potential1, while several other studies put this figure around 20%2,3. And as a cumulative effect, all malnourished children, create a huge impact on the National economy due to their reduced earning potential.4 Malnutrition in Pakistan is the severest in the region. Thus inferred, chronic malnutrition has been incurring a loss of three per cent of GDP per year through lack of optimum productivity, which makes the problem of malnutrition worse than the energy crisis that costs two per cent of the GDP in Pakistan annually. Malnutrition is a life and death crisis for many. The World Health Organization (WHO) says that malnutrition is by far the largest contributor to child mortality globally, currently present in 45 percent of all cases.5More than 350,000 children die in Pakistan every year before their fifth birthday and 35% of these deaths are due to malnutrition. Adequate food and nutrition is the right of every citizen as enshrined in Article 38 of the Constitution of Pakistan which states that “The State shall provide basic necessities of life, such as food, clothing, housing, education and medical relief”. The Punjab government enacted the Punjab Protection of Breastfeeding and Young Child Nutrition (Amendment) Act 2012, however, it is important to notify the rules of the law and the Infant Feeding Board to monitor its implementation. The statistics gathered from various United Nation (UN) and donor sources indicated that Pakistan ranks below China, India, Bangladesh and Sri Lanka on prevalence of stunting, micronutrient uptake, adolescent and adult nutrition status and various other indicators directly related with nutrition.Delayed growth, especially stunting, is reported in children with clinical signs of vitamin A deficiency. A deficiency of zinc, essential for DNA and protein synthesis, leads to growth failure and delayed secondary sexual maturation. A balanced diet could provide these essential nutrients to the population; another way of providing these essential minerals is fortifying staple foods.More than a third of all child deaths every year around the world can easily be attributed to malnutrition, specifically under nutrition, which weakens the body’s resistance to illness. These malnourished and stunted children cannot be expected to grow up as productive adults when compared with those that were fed adequate food in the first five years of life, such nutritional deficiencies can easily be addressed at a nominal cost and the yields are enormous.According to a report ‘Food For Thought’ by Save The Children, children who suffer from malnutrition on an average, score seven percent lower on math tests than non-stunted children; are 19 percent less likely to be able to read a simple sentence by the age of eight, and 12 percent less likely to be able to write a simple sentence. Stunted children are also 13 percent less likely to be in the appropriate grade for their age at school.6A women oriented approach needs to be adopted in response to the situation of malnutrition in high risk districts of South Punjab with a focus on birth spacing and iron supplementation. Given the circumstances in our country, there is a need to give repeated calls to action and relentless pressure from the civil society to help tackle the issue. Everyone, the government, NGOs, the Public, everyone needs to be made aware of this dire situation, and everyone needs to be rallied together to fight this menace, for the children, for their future, for our future, and for our country’s future.